Expanded Analysis of 20 Pneumococcal Serotypes Associated With Radiographically Confirmed Community-acquired Pneumonia in Hospitalized US Adults. (13th May 2021) - Isturiz, Raul; Grant, Lindsay; Gray, Sharon; Alexander-Parrish, Ronika; Jiang, Qin; Jodar, Luis; Peyrani, Paula; Ford, Kimbal D; Pride, Michael W; Self, Wesley H; Counselman, Francis; Volturo, Gregory; et al.
Abstract: Background: Streptococcus pneumoniae is a causative agent of community-acquired pneumonia (CAP). The 13-valent pneumococcal conjugate vaccine (PCV13) has significantly decreased the burden of PCV13-serotype pneumococcal disease; however, disease from nonvaccine serotypes remains substantial. A recent study documented the persistence of PCV13 serotypes among US adults hospitalized with radiographically confirmed CAP. The current analysis used a recently developed urinary antigen detection (UAD) assay (UAD2) to extend these results to additional serotypes included in an investigational PCV20 vaccine. Methods: This prospective study enrolled adults aged ≥18 years hospitalized with radiographically confirmed CAP between October 2013 and September 2016. Presence of S pneumoniae was determined by blood and respiratory sample culture, BinaxNOW urine testing, and UAD. In addition to Quellung on cultured isolates when available, serotypes were identified from urine specimens using UAD1 for PCV13 serotypes and UAD2 for 7 PCV20-unique serotypes (8, 10A, 11A, 12F, 15B, 22F, and 33F) and 4 additional serotypes (2, 9N, 17F, and 20). Results: Among 12 055 subjects with radiographically confirmed CAP, 1482 were positive for S pneumoniae . PCV13- and PCV20-unique serotypes were associated with 37.7% (n = 559) and 27.0% (n = 400) of cases, respectively; 288 subjects were exclusively diagnosed as positive for S pneumoniae by UAD2. Demographic and clinical disease characteristics were similar between subjects with CAP caused by PCV13 and PCV20-unique serotypes. Conclusions: The current analysis using UAD2 identified a sizeable proportion of hospitalized adult CAP associated with PCV20-unique serotypes. PCV20 may therefore address the burden of CAP caused by the additional serotypes present in the vaccine. Abstract : A novel urinary antigen detection assay substantially increased detection of non-pneumococcal conjugate vaccine 13 (PCV13) serotypes included in an investigational PCV20 among US adults with community-acquired pneumonia (CAP). PCV20 may address the burden of CAP due to the additional serotypes.